Editorial. - Thomson, Peter (Studies in Theatre & Performance, 2014)
The author discusses the differences in the presentation of the "Studies in Theatre and Performance" journal after it has changed its publisher from Intellect Ltd. to Routledge Taylor & Francis Group. He mentions the adoption of the digital revolution of the journal where individual articles will be published first online before in print. He notes that Intellect accommodated a limited number of coloured images in the print-run while Routledge's illustrations in colour will appear online only.